2016
DOI: 10.1504/ijtm.2016.078570
|View full text |Cite
|
Sign up to set email alerts
|

Appropriability: a key to opening innovation internationally?

Abstract: This study focuses on the tense appropriability-openness relationship, defined by some as paradox. Based on an international survey of 415 manufacturing firms, we investigate how the use of different kinds of intellectual property protection mechanisms (IPPMs) affects interfirm R&D collaboration while considering partner location in the analysis as well. Our results show that the use of formal, semi-formal or informal IPPMs has different effects on openness in terms of partner variety and depth of collaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…; Read et al . ; Stefan and Bengtsson ). The identification of this new set of factors makes a contribution to the Smith and Lewis framework by adding a new type of dynamics (see Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Read et al . ; Stefan and Bengtsson ). The identification of this new set of factors makes a contribution to the Smith and Lewis framework by adding a new type of dynamics (see Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Our literature review has identified factors such as trust, patents or R&D intensity that can spur virtuous and vicious cycles, depending on the extent to which these factors occur in the IOR (e.g. Bönte 2008;Gander et al 2007;Li et al 2008;Read et al 2014;Stefan and Bengtsson 2016). The identification of this new set of factors makes a contribution to the Smith and Lewis framework by adding a new type of dynamics (see Figure 2).…”
Section: Factors Spurring Both Virtuous and Vicious Cyclesmentioning
confidence: 99%
“…In general, there seems to be a consensus in the literature that a firm's openness in innovation is curvilinearly related to its appropriation strategy (Huang, Rice, Galvin, & Martin, 2014;Laursen & Salter, 2014;Miozzo, Desyllas, Lee, & Miles, 2016;Stefan & Bengtsson, 2016;Zobel et al, 2017). Thus, interestingly, permeable efficiency boundaries do not equate to a looser appropriation regime.…”
Section: Permeability Of Efficiency Boundariesmentioning
confidence: 99%
“…Firms can use a variety of both formal (patents, trademarks, copyrights, design rights) and informal (secrecy, lead time, process/product complexity, employee retention) appropriation mechanisms in interactions with their partners (Arora, Athreye, & Huang, 2016;Hagedoorn & Zobel, 2015;Huang et al, 2014;Wadhwa et al, 2017). Formal and informal mechanisms are selectively employed across openness dimensions (breadth vs. depth of collaborations) (Zobel et al, 2017) and across national versus international partners (Stefan & Bengtsson, 2016).…”
Section: Permeability Of Efficiency Boundariesmentioning
confidence: 99%
“…National collaborations are found to be successfully under semi-formal and informal IPR regimes with contracts as the main structuring of partnerships, while formal regimes like patents explain international collaborations (Stefan and Bengtsson, 2016). Semi-formal regimes in this setting may be trade secrets and nondisclosure contracts associated with collaboration with both academic partners and companies.…”
Section: Innovation Theorymentioning
confidence: 99%